2017
DOI: 10.1126/science.aan3684
|View full text |Cite
|
Sign up to set email alerts
|

A worldwide survey of neonicotinoids in honey

Abstract: Growing evidence for global pollinator decline is causing concern for biodiversity conservation and ecosystem services maintenance. Neonicotinoid pesticides have been identified or suspected as a key factor responsible for this decline. We assessed the global exposure of pollinators to neonicotinoids by analyzing 198 honey samples from across the world. We found at least one of five tested compounds (acetamiprid, clothianidin, imidacloprid, thiacloprid, and thiamethoxam) in 75% of all samples, 45% of samples c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
267
4
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 398 publications
(285 citation statements)
references
References 79 publications
11
267
4
3
Order By: Relevance
“…Chronic pesticide exposure is increasingly likely to occur in the field as water‐soluble systemic pesticides have been found to occur in wild flowers on field margins (Botias et al., ), and in flowers sold in garden centres (Lentola et al., ), while pesticide products are freely available for gardeners to purchase, and bees preferentially feed on sucrose solutions that have been treated with pesticides (Kessler et al., ). Our results draw together a body of evidence that in combination suggests the rising prevalence of pesticides in the environment (Mitchell et al., ) is increasingly likely to influence the cognitive abilities of bees.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic pesticide exposure is increasingly likely to occur in the field as water‐soluble systemic pesticides have been found to occur in wild flowers on field margins (Botias et al., ), and in flowers sold in garden centres (Lentola et al., ), while pesticide products are freely available for gardeners to purchase, and bees preferentially feed on sucrose solutions that have been treated with pesticides (Kessler et al., ). Our results draw together a body of evidence that in combination suggests the rising prevalence of pesticides in the environment (Mitchell et al., ) is increasingly likely to influence the cognitive abilities of bees.…”
Section: Discussionmentioning
confidence: 99%
“…However, neonicotinoids have been implicated as a threat to eusocial bees (Gill et al, 2012;Goulson, 2013;Lundin, Rundlöf, Smith, Fries, & Bommarco, 2015;Tsvetkov et al, 2017;Whitehorn, O'Connor, Wackers, & Goulson, 2012;Woodcock et al, 2017). Foraging eusocial bees are frequently exposed to neonicotinoids in treated landscapes (Botías, David, Hill, & Goulson, 2017;Botías et al, 2015;David et al, 2016;Mitchell et al, 2017;Rolke, Persigehl, Peters, Sterk, & Blenau, 2016), and controlled exposure experiments have demonstrated impaired homing ability (Fischer et al, 2014) and foraging efficiency of workers, including longer foraging trips and reduced rate of pollen collection (Feltham, Park, & Goulson, 2014;Gill & Raine, 2014;Stanley & Raine, 2016). A possible explanation for these reported impairments is that certain aspects of foraging flight dynamics, such as endurance and speed, are affected by neonicotinoid exposure.…”
Section: Introductionmentioning
confidence: 99%
“…For this study, we exposed individual workers to the neonicotinoid imidacloprid at a concentration of 10 ppb as it is: (a) a widely used insecticide across the globe with a growing market in many regions (Auteri et al, 2017;Casida, 2018;Cressey, 2017;Mitchell et al, 2017;Zhang, 2018); (b) a concentration that can be found inside social bee colonies, on return foraging workers, and in the pollen and nectar of individual flowers (Blacquière, Smagghe, van Gestel, & Mommaerts, 2012;Cresswell, 2011;Dively & Kamel, 2012;Goulson, 2013;Hladik, Vandever, & Smalling, 2016);…”
Section: Introductionmentioning
confidence: 99%
“…Thiamethoxam (THI) is a widely prevalent neonicotinoid in nectar, honey, and pollen from both agricultural crops as well as non‐target species at median doses in seed‐treated oilseed rape nectar from 0.65 to 2.4 μg kg –1 , at mean doses in honey from 0.29 to 6.4 μg kg –1 , to as high as 17.2 μg kg –1 , and at mean doses in pollen from 0.15 to 28.9 μg kg –1 . In semi‐field studies, chronic exposure to environmental doses of THI, as well as its metabolite clothianidin (CLO), another neonicotinoid insecticide, have been linked to deleterious, sublethal effects on honey bees, including decreased queen fecundity (at doses of 4 μg kg –1 THI and 1 μg kg –1 CLO) and decreased colony honey production (at doses of 20 μg kg –1 CLO), but field studies often find no effect of environmental THI or CLO exposure on honey bee colonies …”
Section: Introductionmentioning
confidence: 99%